ChemInform Abstract: A Green Approach for the Regio‐ and Stereo‐Selective Syntheses of (Z)‐3‐Methyleneisoindoline‐1‐ones in Aqueous Medium. Issue 43 (7th October 2013) - Chatterjee, Nivedita; Sarkar, Swarbhanu; Pal, Rammyani; Sen, Asish Kumar
Abstract A novel method for the synthesis of the title species through copper‐free domino Sonogashira cross‐coupling/5‐exo‐dig‐cyclization reaction of sulfonates (I) with terminal alkynes (II) is developed.